Alkaline pure water electrolysis oxygen desorption reaction electrode material as well as synthesis method and application thereof
By using the solution impregnation method on the nickel substrate to generate a dense catalytic layer containing nickel, tin or hydroxide, to form an electrode material with a two-dimensional nanosheet-like array structure, the problems of high cost, low abundance and poor stability of OER catalysts in the prior art are solved, and efficient and stable alkaline pure water electrolytic oxygen reaction is achieved.
Patent Information
- Application Number
- CN202510245113.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-04
AI Technical Summary
The prior art design of efficient redox reaction (OER) catalysts in alkaline media has problems of high cost, low abundance and poor stability, which limits its industrial application in the electrochemical water decomposition process.
An alkaline pure water electrolytic oxygen reaction electrode material consisting of a nickel substrate and a dense catalytic layer containing nickel, tin or hydroxide generated by solution impregnation is formed to form a uniform and dense two-dimensional nanosheet-like array structure.
This electrode material exhibits electrocatalytic performance and excellent stability in alkaline pure water electrolytes, and has no significant decrease in catalytic activity after long-term operation. It can achieve efficient OER in 1M KOH medium, with low overpotential and long stability.
Smart Images

Figure CN119736653A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of two-dimensional nanomaterials containing tin and nickel, and specifically relates to an alkaline pure water electrolysis oxygen reaction electrode material and a synthesis method and application thereof. Background Art
[0002] Among various hydrogen production technologies, the use of intermittent renewable energy (such as solar energy, wind energy, and tidal energy) to drive electrochemical water decomposition to produce hydrogen shows significant application potential due to its clean, green, and pollution-free characteristics.
[0003] The electrochemical water splitting process includes two key half reactions: hydrogen evolution reaction (HER) at the cathode and oxygen evolution reaction (OER) at the anode. Compared with the two-electron transfer process of HER, OER involves a complex four-electron transfer pathway accompanied by OH - A series of reaction steps, such as the adsorption and dissociation of O, the formation of OO intermediates, and the desorption of O2, lead to significantly slow kinetics, which becomes the bottleneck of the entire electrochemical water splitting process. Therefore, how to design and develop efficient OER catalysts and improve the reaction kinetic efficiency is the key to promoting the development of electrochemical water splitting hydrogen production technology. It is worth noting that in alkaline media, since the OH⁻ concentration is much higher than that in acidic or neutral media, the OER reaction kinetics are significantly improved, and alkaline conditions are considered to be more conducive to the realization of electrochemical water splitting. Although noble metal catalysts based on IrO2 and RuO2 show excellent catalytic performance in OER, their high cost, low abundance, and poor long-term stability have greatly limited their industrial application. Therefore, the development of highly active, low-cost and stable OER catalysts based on earth-abundant elements has become the core goal of research and application of alkaline water electrolysis technology. In recent years, non-noble metal-based materials have gradually become a research hotspot due to their low cost, excellent catalytic performance and good stability. Among them, nickel-based layered double hydroxide (Ni-LDH) shows broad prospects for industrial application due to its easy synthesis, remarkable structural stability and excellent OER activity. By regulating the structure of Ni-LDH and optimizing the surface chemical environment, its catalytic activity can be further improved and its service life can be extended. Therefore, the development of highly active, low-cost and stable OER catalysts based on earth-abundant elements has become the key to promoting the development of alkaline water electrolysis technology. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide an alkaline pure water electrolysis oxygen decomposition reaction electrode material and its synthesis method and application. The electrode material has better electrocatalytic performance and excellent stability than the original substrate in alkaline pure water electrolyte, and the catalytic activity does not decrease significantly after long-term operation. It is an alkaline pure water electrolysis electrode material with broad prospects.
[0005] To achieve the above object, the technical solution of the present invention is as follows: The invention provides an alkaline pure water electrolysis oxygen decomposition reaction electrode material, which comprises a nickel substrate and a surface dense catalytic layer in situ generated on the nickel substrate by a solution impregnation method, wherein the surface dense catalytic layer is an oxide or hydroxide containing nickel and tin.
[0006] Furthermore, the electrode material has a uniform and dense two-dimensional nanosheet array structure, and the lateral thickness of the sheet is 20 to 60 nm and the longitudinal length is 200 to 500 nm.
[0007] The present invention provides a method for synthesizing an electrode material for an alkaline pure water electrolysis oxygen reaction, comprising the following steps: 1) First, the nickel substrate is pretreated, and the treated nickel substrate is stored in a vacuum drying oven; 2) Containing Sn 4+ The metal salt is dissolved in deionized water and stirred until completely dissolved to obtain a precursor solution; 3) The nickel substrate obtained in step 1) is completely immersed in the precursor solution prepared in step 2) and allowed to stand for a period of time. After standing, the nickel electrode is taken out and dried to obtain an electrode material for alkaline pure water electrolysis oxygen reaction.
[0008] Further, step 1) the nickel substrate pretreatment process is as follows: Acetone, acid solution, deionized water and anhydrous ethanol are used as cleaning agents for the nickel substrate, respectively, and ultrasonicated for 5 to 15 minutes in an ultrasonic environment to remove organic matter, oxides and acids on the surface of the substrate; the acid solution includes HCl, H2SO4 or HNO3.
[0009] Furthermore, in step 1), the nickel substrate is nickel foam, nickel mesh or nickel foil.
[0010] Furthermore, step 2) contains Sn 4+ The metal salt is tin tetrachloride, tin fluoride, tin tetrachloride hydrate or tin fluoride hydrate; the concentration of the tin salt is 0.05~0.5M, and the stirring time is 10~60min.
[0011] Furthermore, in step 2), the concentration of the tin salt is 0.1-0.2 M; and the stirring time is 15-30 min.
[0012] Furthermore, in step 3), the immersion time is 15 to 240 min; the immersion temperature is 20 to 80°C; and the drying temperature is 20 to 100°C.
[0013] Furthermore, in step 3), the immersion time is 30 to 120 min; the immersion temperature is 40 to 60°C; and the drying temperature is 60 to 80°C.
[0014] The invention also proposes an electrode material prepared by the synthesis method as an electrode material for alkaline pure water electrolysis oxygen decomposition reaction.
[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The present invention first pre-treats the nickel substrate, and the treated nickel substrate is stored in a vacuum drying oven; then 4+ The metal salt is dissolved in deionized water and stirred until completely dissolved to obtain a precursor solution; then the nickel substrate is completely immersed in the prepared precursor solution and allowed to stand for a period of time, after which the nickel electrode is taken out and dried to obtain an electrode material for alkaline pure water electrolysis oxygen reaction, wherein the electrode material has a uniform and dense two-dimensional nanosheet array structure; 2) The electrode material synthesized by the method of the present invention has a good catalytic effect on the electrolytic oxygen separation reaction of alkaline simulated seawater. In 1M KOH medium, 10 mA cm -2 The overpotential at the current density is only 300 ~ 330 mV, and in 1M KOH medium, 500 mA cm -2 The stability at the current density can last up to 24h without deactivation; 3) The synthesis method of the present invention is simple and easy. The synthesized electrode material has better electrocatalytic performance and excellent stability than the original substrate in alkaline pure water electrolyte. There is no obvious decrease in catalytic activity after long-term operation. It is a promising alkaline pure water electrolysis electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 X-ray diffraction patterns of Sn@NF electrode materials prepared in Examples 1, 2, and 3 of the present invention; Figure 2 This is a scanning electron microscope image of the Sn@NF electrode material prepared in Example 1 of the present invention. Figure 2 Figure (a) and Figure 2 The middle (b) image is a scanning electron microscope image of Sn@NF (0.2M) at different magnifications in the same area; Figure 3 The linear sweep voltammetry curves of Sn@NF (0.2M) and NF prepared in Example 1 of the present invention; Figure 4 The linear sweep voltammetry curves of Sn@NF (0.05M) and NF prepared in Example 2 of the present invention; Figure 5 The linear sweep voltammetry curves of Sn@NF (0.1M) and NF prepared in Example 3 of the present invention; Figure 6The Sn@NF (0.2 M) and NF electrode prepared in Example 1 of the present invention were subjected to 500 mA cm in 1 M KOH. -2 Two-electrode stability test of current density; Figure 7 The Sn@NF (0.05 M) and NF electrode prepared in Example 2 of the present invention were subjected to 500 mA cm in 1 M KOH. -2 Two-electrode stability test of current density; Figure 8 The Sn@NF (0.1 M) and NF electrode prepared in Example 3 of the present invention were subjected to 500 mAcm in 1 M KOH. -2 Two-electrode stability test of current density. DETAILED DESCRIPTION
[0017] The present invention will be further described below in conjunction with embodiments, but the scope of protection of the present invention is not limited to the described scope. Example 1
[0018] In this embodiment, the preparation method of Sn@NF electrode material obtained by treating nickel foam with tin metal solution is as follows: 1) Preparation and preservation method of pretreated nickel foam (NF): Acetone, 2 M HCl, deionized water, and anhydrous ethanol were used as cleaning agents, respectively, and ultrasonicated for 10 min in an ultrasonic environment to remove NF (3×2 cm 2 )Organic matter, oxides, and acids on the substrate surface. The treated NF substrate is stored in a vacuum drying oven to avoid oxidation by air; 2) Weigh 10 mM (3.506 g) SnCl4·5H2O and dissolve it in 50 ml deionized water. Stir until completely dissolved. 3) The pretreated NF substrate was completely immersed in the precursor solution at a temperature of 60°C, taken out after immersion for 60 min, and vacuum dried at 60°C overnight. The obtained electrode material sample was labeled Sn@NF (0.2M).
[0019] The electrode material prepared above was subjected to X-ray diffraction analysis. Figure 1 As shown in the figure, it can be observed that the characteristic peak position of its XRD matches the standard single nickel XRD, and there is no obvious characteristic peak of Sn species, indicating that the material has low crystallinity or an amorphous structure.
[0020] The electrode material prepared above was subjected to morphological analysis, and its scanning electron microscope image is as follows Figure 2 As shown, the material has a uniform and dense two-dimensional nanosheet array structure with a nanosheet thickness of 20 to 60 nm, and the nanosheet can expose more active sites.
[0021] The Sn@NF (0.2M) electrode material prepared by treating nickel foam with the above tin metal solution was applied to the anode oxygen evolution reaction (OER) electrode material in alkaline pure water electrolysis to evaluate the electrochemical performance. The test method is as follows: The Sn@NF (0.2M) electrode material (2×3 cm 2 ), cut into 1×1 cm 2 ; Use a platinum sheet electrode clamp to clamp one side of the electrode material to fix it; use a standard three-electrode system for testing, the prepared electrode material Sn@NF (0.2M) is the working electrode, and the counter electrode is a platinum foil 1×1 cm 2 The reference electrode was Hg / HgO (0.098 V vs. RHE), the electrolyte was 1 M KOH, and the effective working area was kept at 1 cm 2 The electrodes were first activated by cyclic voltammetry (CV) in 1 M KOH electrolyte with a voltage setting range of 0.1 V to 1.0 V and a scan rate of 50 mV·s -1 50 cycles were performed; then a linear sweep voltammetry (LSV) test was performed in the electrolyte with a voltage setting range of 0 V to 1.2 V vs. Hg / HgO and a scan rate of 5 mV·s -1 Then, the material was subjected to EIS test at a voltage of 0.65 V vs. Hg / HgO and a frequency of 100 kHz to 0.01 Hz to obtain the solution (1 M KOH) resistance. Finally, a two-electrode system was used in a 1 M KOH electrolyte at a constant current of 500 mA cm -2 The long-term stability of Sn@NF (0.2M) electrode material was tested under the following conditions.
[0022] Test results such as Figure 3 and Figure 6 As shown in the figure, it can be seen that at 10 mA cm -2 The lower overpotential is only 304mV, 500mA cm -2 The stability under high temperature can reach 24h. Therefore, the catalyst is an electrode material with high activity and long-term stability for the oxygen evolution reaction (OER) in alkaline pure water. Example 2
[0023] In this embodiment, the preparation method of Sn@NF electrode material obtained by treating nickel foam with tin metal solution is as follows: 1) Preparation and preservation method of pretreated nickel foam (NF): Acetone, 2 M HCl, deionized water, and anhydrous ethanol were used as cleaning agents, respectively, and ultrasonicated for 10 min in an ultrasonic environment to remove NF (3×2 cm 2)Organic matter, oxides, and acids on the substrate surface. The treated NF substrate is stored in a vacuum drying oven to avoid oxidation by air; 2) Weigh 2.5 mM (0.877 g) SnCl4·5H2O and dissolve it in 50 ml deionized water. Stir until completely dissolved. 3) The pretreated NF substrate was completely immersed in the precursor solution at a temperature of 80°C, taken out after immersion for 90 min, and vacuum dried at 60°C overnight. The obtained catalyst sample was labeled Sn@NF (0.05M).
[0024] The Sn@NF (0.05M) electrode material prepared by treating nickel foam with the above-mentioned tin metal solution was applied to the alkaline pure water electrolysis anodic oxygen evolution reaction (OER) electrode material for electrochemical performance evaluation. The test method was as follows: the same as Example 1.
[0025] Test results such as Figure 4 and Figure 7 As shown in the figure, it can be seen that at 10 mA cm -2 The lower overpotential is only 326mV, 500mA cm -2 The stability can last up to 24 hours. Example 3
[0026] In this embodiment, the preparation method of Sn@NF electrode material obtained by treating nickel foam with tin metal solution is as follows: 1) Preparation and preservation method of pretreated nickel foam (NF): Acetone, 2 M HCl, deionized water, and anhydrous ethanol were used as cleaning agents, respectively, and ultrasonicated for 10 min in an ultrasonic environment to remove NF (3×2 cm 2 )Organic matter, oxides, and acids on the substrate surface. The treated NF substrate is stored in a vacuum drying oven to avoid oxidation by air; 2) Weigh 5 mM (1.753 g) SnCl4·5H2O and dissolve it in 50 ml deionized water. Stir until completely dissolved. 3) The pretreated NF substrate was completely immersed in the precursor solution at a temperature of 60°C, taken out after immersion for 120 min, and vacuum dried at 60°C overnight. The obtained catalyst sample was labeled Sn@NF (0.1M).
[0027] The Sn@NF (0.1M) electrode material prepared by treating nickel foam with the above-mentioned tin metal solution was applied to the alkaline pure water electrolysis anodic oxygen evolution reaction (OER) electrode material for electrochemical performance evaluation. The test method was as follows: the same as Example 1.
[0028] Test results such as Figure 5 and Figure 8 As shown in the figure, it can be seen that at 10 mA cm-2 The lower overpotential is only 300mV, 500mA cm -2 The stability can last up to 24 hours.
[0029] Comparative Example 1: 1) Preparation and preservation method of pretreated nickel foam (NF): Acetone, 2 M HCl, deionized water, and anhydrous ethanol were used as cleaning agents, respectively, and ultrasonicated for 10 min in an ultrasonic environment to remove NF (3×2 cm 2 )Organic matter, oxides, acids, etc. on the substrate surface. The treated NF substrate is stored in a vacuum drying oven to avoid oxidation by air; 2) Take 50 ml of deionized water and heat it to 60°C. Completely immerse the pretreated NF substrate in the deionized water at 60°C. Take it out after immersion for 60 min and vacuum dry it at 60°C overnight. The obtained electrode material sample is labeled NF-1.
[0030] The NF-1 electrode material prepared as above was applied to the alkaline pure water electrolysis anodic oxygen evolution reaction (OER) electrode material to evaluate the electrochemical performance. The test method was as follows: the same as in Example 1.
[0031] Test results such as Figure 3~Figure 5 and Figure 6~Figure 8 As shown in the figure, it can be seen that at 10 mA cm -2 The lower overpotential is 367 mV, 500 mA cm -2 The stability under the condition was inactivated after only 0.75h.
Claims
1. An alkaline pure water electrolysis oxygen reaction electrode material, characterized in that The electrode material comprises a nickel substrate and a surface dense catalytic layer in-situ generated on the nickel substrate by a solution impregnation method, wherein the surface dense catalytic layer is an oxide or hydroxide containing nickel and tin.
2. The alkaline pure water electrolysis oxygen reaction electrode material according to claim 1, characterized in that The electrode material has a uniform and dense two-dimensional nanosheet array structure, with a lateral thickness of 20 to 60 nm and a longitudinal length of 200 to 500 nm.
3. A method for synthesizing an electrode material for alkaline pure water electrolysis of oxygen as claimed in any one of claims 1 to 2, characterized in that The steps include: 1) First, the nickel substrate is pretreated, and the treated nickel substrate is stored in a vacuum drying oven; 2) Containing Sn 4+ The metal salt is dissolved in deionized water and stirred until completely dissolved to obtain a precursor solution; 3) The nickel substrate obtained in step 1) is completely immersed in the precursor solution prepared in step 2) and allowed to stand for a period of time. After standing, the nickel electrode is taken out and dried to obtain an electrode material for alkaline pure water electrolysis oxygen reaction.
4. The method for synthesizing an electrode material for alkaline pure water electrolysis of oxygen according to claim 3, characterized in that Step 1) The nickel substrate pretreatment process is as follows: Acetone, acid, deionized water and anhydrous ethanol are used as cleaning agents for the nickel substrate, respectively, and ultrasonicated for 5 to 15 minutes in an ultrasonic environment to remove organic matter, oxides and acids on the surface of the substrate; the acid includes HCl, H2SO4 or HNO3.
5. The method for synthesizing the electrode material for alkaline pure water electrolysis oxygen decomposition reaction according to claim 3, characterized in that In step 1), the nickel substrate is nickel foam, nickel mesh or nickel foil.
6. The method for synthesizing an electrode material for alkaline pure water electrolysis of oxygen according to claim 3, characterized in that Step 2) contains Sn 4+ The metal salt is tin tetrachloride, tin fluoride, tin tetrachloride hydrate or tin fluoride hydrate; the concentration of the tin salt is 0.05~0.5M, and the stirring time is 10~60min.
7. The method for synthesizing electrode materials for alkaline pure water electrolysis of oxygen according to claim 6, characterized in that Step 2) The concentration of tin salt is 0.1~0.2M; the stirring time is 15~30 min.
8. The method for synthesizing electrode materials for alkaline pure water electrolysis of oxygen according to claim 3, characterized in that In step 3), the immersion time is 15 to 240 min; the immersion temperature is 20 to 80°C; and the drying temperature is 20 to 100°C.
9. The method for synthesizing an electrode material for alkaline pure water electrolysis of oxygen according to claim 8, characterized in that In step 3), the immersion time is 30 to 120 min; the immersion temperature is 40 to 60°C; and the drying temperature is 60 to 80°C.
10. An electrode material prepared by the synthesis method according to any one of claims 3 to 9 as an electrode material for alkaline pure water electrolysis of oxygen.
Citation Information
Patent Citations
Method for preparing 3D acicular nickel-cobalt bimetallic oxide nano-cluster by one-step electro-deposition method
CN110706944A
Three-dimensional reticular nano-structure material assembled by Sn-doped nickel hydroxyl phosphite nanowires, and preparation method and application of three-dimensional reticular nano-structure material
CN111889119A
Composite porous filtration-catalysis material and preparation method thereof
CN112892551A
Metal doped tin oxide and preparation method and application thereof
CN116426968A
Cobalt-iron layered double hydroxide growing on foamed nickel in situ, preparation method and application of cobalt-iron layered double hydroxide
CN116815231A